(untitled) (Research, Society and Development, 2021)
Objective: Describe the practice of free time physical activity among adults in Brazil from 2011 to 2019. Materials and Methods: Descriptive ecological epidemiological study, using secondary data from the Risk and Protection Factors Surveillance System for Chronic Diseases by Telephone Survey in the period from 2011 to 2019. The population consisted of adults (≥ 18 years old). The following variables were chosen: year, sex, capital, region, age group and education. Results: In the period analyzed, the South (39.6%), Midwest (39.6%) and North (39.2%) regions had the highest average of physical activity. Florianópolis, Distrito Federal and Palmas were the capitals that presented the highest index of physical activity. It was observed that the practice of physical activity during leisure was higher in males (45.9%), in the age group of 18 to 24 years (48.1%) and in individuals who had 9 or more years of study. Conclusion: Men, young adults and individuals with a higher level of education had better rates of physical activity during leisure time. Higher prevalence of physical activity in the cities of Florianópolis, Palmas and the Federal District and in the South, Midwest and North regions.